APPRAISING ENVIRONMENTAL CRISIS: AN ECOLINGUISTIC EVALUATION OF THE LOS ANGELES WILDFIRE COVERAGE IN NATIONAL GEOGRAPHIC MAGAZINE - Mardliya Pratiwi Zamruddin; Famala Eka Sanhadi Rahayu; Ahmad Mubarok; Jonathan Irene Sartika Dewi Max (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
Environmental crises are increasingly mediated through global media platforms, shaping public perception and ecological awareness. National Geographic, as a prominent environmental outlet, plays a key role in constructing narratives around ecological issues. However, the linguistic strategies it employs—particularly evaluative language—remain underexplored. This study aims to investigate the evaluation of LA Wildfire in National Geographic Magazine through an ecolinguistic framework. The study is designed as qualitative research with a content analysis approach, which analyzed four articles discussing LA Wildfire 2025 in the National Geographic Magazine in the Environmental Section. The analysis focuses on appraisal patterns which cover three aspects: attitude, engagement, and graduation where each aspects has their sub categories which makes this analysis detailed. The findings reveal a dominant use of appreciation and judgment to evoke urgency and moral responsibility, while affect is comparatively minimized. Salience patterns foreground scientific authority and global impact, often marginalizing local ecological voices. Metaphors such as “tipping point” and “planetary fever” reinforce crisis framing but risk oversimplifying complex ecological dynamics. This study contributes to ecolinguistics by demonstrating how evaluative language in environmental media can both amplify ecological concern and obscure systemic causes, highlighting the need for more reflexive and inclusive environmental storytelling.